PCR-RFLP ANALYSIS OF INSULIN-LIKE GROWTH FACTOR-1 GENE OF KALAHARI RED GOATS - Kwena Mokoena; Thobela Louis Tyasi; Vusi Mbazima (Journal of Animal and Plant Sciences, 2023)
Insulin-like growth factor 1 gene (IGF-1) is associated with growth traits in different livestock, but its association with growth traits in South African indigenous goat breeds is poorly understood. The study's objective was to identify the single nucleotide polymorphisms (SNPs) of IGF-1 in the Kalahari Red goat breed and their association with the growth traits. Two genotypes (KK and KM) were identified using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The frequency of genotype KK and KM was 0.56 and 0.44 respectively. The allelic frequency of allele K and M was 0.78 and 0.22 respectively. The studied Kalahari Red goat breed population was not in Hardy Weinberg equilibrium (HWE) as revealed by the Chi-square test (χ2 = 0.39). Marker-trait association indicated that the identified genotypes had no association (P > 0.05) with the measured growth traits. In conclusion, the current study suggests that two identified genotypes of IGF-1 might not be used as potential genetic markers during selection to improve growth traits. Further studies need to be conducted on SNPs of IGF-1 and their association with growth traits using a larger sample, more growth traits and targeting more exons ofKalahari Red goats.
Keywords: Single nucleotide polymorphisms; Body weight; Genetic markers; Hardy Weinberg equilibrium